Effect of a compound nutrition preparation on wound healing after acute trauma in rats - XIN Wenbin; BAI Qian; NI Xiangmin (陆军军医大学学报)
Objective‍　‍To explore the efficacy of a compound nutrition preparation on wound healing after acute trauma and investigate the underlying mechanism primarily. Methods‍　‍After skin wound model was successfully constructed on totally 60 male SD rats surgically, they were randomly divided into control group (CON group), whey protein group (WP group) and low- and high-dose nutritional formula groups (LDF and HDF groups), with 15 animals in per group. From the next day after surgery, the rats in each group were given corresponding nutritional interventions for 2 weeks. During the intervention, the wound conditions were observed and recorded, and the wound area was measured. The samples were collected on the 3rd, 7th and 14th days after surgery, respectively. Serum albumin (ALB), prealbumin (PA), total protein (TP), inflammatory factors (TNF-α, IL-1β, IL-6 and IL-10), immunoglobulins (IgA, IgG and IgM) and hydroxyproline (Hyp) were detected by the corresponding reagent kits. The histopathologic changes of wound were observed with HE staining. Masson staining was used to observe the collagen fiber deposition in wound tissue. The angiogenesis of wound tissue was evaluated by immunohistochemical staining. Results‍　‍Compared with the CON group, the wound healing speed, collagen synthesis and angiogenesis speed were significantly accelerated in the WP group, LDF group and HDF group (P<0.05), and the effects were the most obvious in the HDF group. On the 3rd day after surgery, in the WP, LDF and HDF groups, the serum ALB, PA and TP levels were significantly increased (P<0.05), serum TNF-α and IL-1β levels were obviously decreased (P<0.05), and serum IL-10 level was notably increased (except WP group) when compared with the CON group. The serum IgG and IgM levels were significantly increased in the LDF group and HDF group (P<0.05) and significant increment of IgA was only observed in the HDF group (P<0.05). On the 7th day after modeling, the levels of ALB, PA and TP were significantly increased (P<0.05), the levels of TNF-α, IL-1β and IL-6 were obviously decreased (P<0.05), and the levels of IL-10 were remarkably increased (P<0.05) in the HDF group than the CON group; The LDF group and HDF group had significantly elevated serum IgG and IgM levels (P<0.05), but only the former group had statistically increased serum IgA level (P<0.05). On the 14th day after modeling, the HDF group had significantly increased levels of ALB and TP (P<0.05), decreased levels of IL-1β (P<0.05), and raised levels of IgG and IgM when compared with the CON group (P<0.05). Conclusion‍　‍Our compound nutrition preparation promotes wound healing in rat model of acute trauma, which might be related to its improving the nutritional status, promoting collagen synthesis, and thus alleviating inflammatory response and enhancing immune function.